HYDROGEOLOGICAL STUDY OF THE RIVER CONNECTED AQUIFERS IN GREATER SAO PAULO - Ross, S. D.; Rudolph, D. L.; Ellert, N.; Farvolden, R. N.; Greenhouse, J. F.; Rebouças, A. C. (Águas Subterrâneas, 1990)
inexistente